Impacto de la violencia en la población vulnerable : un acercamiento a la situación de las poblaciones vulnerables en medio del conflicto armado (2008)
ABSTRACT: Without ignore that the conflict situation that prevails in Colombia affects all its inhabitants, it is clear that the consequences of it, is experienced differently and their practices affect some people more than others.